2012
DOI: 10.1111/j.1468-3083.2012.04602.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological differentiation between palmoplantar pustulosis and pompholyx

Abstract: Several histological features could serve as useful 'clues' to differentiate between PPP and pompholyx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
1
37
0
1
Order By: Relevance
“…Histopathologically, PPP is classically characterized by large intra‐epidermal unilocular pustules that represent massive accumulations of neutrophils, while pompholyx presents with spongiosis and intraepidermal vesiculation in the acute phase . According to one recent report meticulously describing both diseases, the loss of the granulation layer often portends PPP, while irregular epidermal hyperplasia and spongiotic vesicle are observed more frequently in pompholyx . Dense immunostaining of epithelial membrane antigen in keratinocytes immediately peripheral to vesicles also more strongly favours a diagnosis of pompholyx rather than PPP …”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, PPP is classically characterized by large intra‐epidermal unilocular pustules that represent massive accumulations of neutrophils, while pompholyx presents with spongiosis and intraepidermal vesiculation in the acute phase . According to one recent report meticulously describing both diseases, the loss of the granulation layer often portends PPP, while irregular epidermal hyperplasia and spongiotic vesicle are observed more frequently in pompholyx . Dense immunostaining of epithelial membrane antigen in keratinocytes immediately peripheral to vesicles also more strongly favours a diagnosis of pompholyx rather than PPP …”
Section: Introductionmentioning
confidence: 99%
“…Exemplarily, difficulties occur when distinguishing seborrheic scalp dermatitis from scalp psoriasis due to psoriasiform hyperplasia and neutrophil infiltration in seborrheic dermatitis or when clarifying the diagnosis of palmoplantar psoriasis and hand eczema. In the latter case, due to the anatomic properties of the palm, histology often provides merely diagnostic clues [2,3].…”
mentioning
confidence: 99%
“…Many reports have described the clinical, histological, immunological and genetic features of PPP patients, but the pathophysiology and etiology remain unclear . Histopathologically, the earliest PPP lesion is a spongiotic vesicle in the lower malpighian layer containing mononuclear cells and some neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al . reported that several histological features such as “loss of granular layer”, “irregular epidermal hyperplasia” and “spongiotic vesicle” could aid in the differential diagnosis of PPP and pompholyx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation